2020
DOI: 10.1038/s41598-020-58632-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Calorie Diet on Intestinal Flora in LPS-Induced Pneumonia Rats

Abstract: Intestinal flora plays an important role in inflammatory response to systemic or local organs of its host. High calorie diet has been shown to aggravate the condition of pneumonia and delay recovery, especially in children. However, the underlying mechanisms remain unclear. This study placed SPF rats in a conventional environment, high calorie diet or LPS atomization was performed respectively or combined. Analysis of high-throughput sequencing of intestinal content combined with animal weight, organ index, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…For example, Zhu et al (2020) used 16S rRNA amplicon sequencing to study the gut microbiota of ulcerative colitis with different glucocorticoid response types and found that they had different bacterial composition and function, which linked the microbiota disorders and ulcerative colitis. Analysis of 16S rRNA amplicon sequencing of intestinal microbiota found that high-calorie diet and lipopolysaccharide atomization synergistically promoted pneumonia process in rat pups, which is related to changes in the structure of intestinal flora ( Bai et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zhu et al (2020) used 16S rRNA amplicon sequencing to study the gut microbiota of ulcerative colitis with different glucocorticoid response types and found that they had different bacterial composition and function, which linked the microbiota disorders and ulcerative colitis. Analysis of 16S rRNA amplicon sequencing of intestinal microbiota found that high-calorie diet and lipopolysaccharide atomization synergistically promoted pneumonia process in rat pups, which is related to changes in the structure of intestinal flora ( Bai et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, variations in the relative abundance of relevant bacterial taxa suggest that the captive environment may impair the mental health of threatened equids to some extent. Planococcaceae were significantly increased and had the highest relative abundance in captive equids, and an animal model study suggests that elevated levels of this bacterium may be associated with a high-calorie diet and may exacerbate local inflammatory responses ( Bai et al, 2020 ). Forage for captive Equidae is mainly alfalfa hay, which, as a high-quality forage grass worldwide used, has a high carbohydrate and protein content ( Scholtz et al, 2009 ; Bouton, 2012 ), as well as a constant supply of feed, which may cause a large caloric intake of captive Equidae, resulting in a dramatic increase in the level of Planococcaceae .…”
Section: Discussionmentioning
confidence: 99%
“…Dietary factors may be related the abundance of HpeI and LPS in the human gut. It has been reported that dietary style, such as Western diet, high calorie diet, high fat diet (HFD), may increase the LPS abundance in both human and mice ( Fuke et al, 2019 ; Bai et al, 2020 ). On the other hand, high-grain diet, probiotics, prebiotics, and polyphenols could reduce the level of LPS in goat liver ( Chang et al, 2015 ; Fuke et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%